Review of existing methods for carbon accounting - Bird, D.N.; Pena, N.; Schwaiger, H.; Zanchi, G. (Center for International Forestry Research, 2010)
Forests are sources of biomass that can be used to create forest-based bioenergy, whether directly by establishing energy plantations on non-forestland, by using existing forest resources or by using residues from harvesting for nonbioenergy purposes. If created in a sustainable manner, this bioenergy can have significant positive greenhouse gas benefits. However, past experience provides strong reason to believe that significant bioenergy development will come at the expense of natural forests, either through direct conversion of forests to non-forestland or through indirect competition between land uses. Bioenergy development may increase the demand for agricultural land, which may be sourced from tropical forests. In this case, the net carbon balance would be highly negative. This paper first reviews existing methods for carbon accounting for forest-based bioenergy development.The review examines methodologies from: 1. the IPCC Good Practice Guidance for Land Use, Land-Use Change and Forestry (GPGLULUCF) and the 2006 IPCC Guidelines for National Greenhouse Gas Inventories (2006 IPCC Guidelines); and 2. Directive 2009/28/EC of the European Parliament and of the Council (EU Renewable Energy Directive).